Ulcerative colitis in Malaysians - Pailoor, Jayalakshmi; Wong, N.W.; Malik, A.K.; Goh, K.L. (Faculty of Medicine, University of Malaya, 1996)
A review of all colonic biopsies received by the Department of Pathol ogy duringa 8-year period revealed 41cases of ulcerative colitis (UC). The diagnosis was based on histological and clinical features. The age range of patients was be tween 14 - 76 years with a median age of 35.4 years. The disease was more prevalent among Indians. The common presenting symptoms were diarrhoea (100%) and haematochezia (83%). The extent of colonic involvement varied. Twelve patients ( 29.2%) had pancolitis and 8 (19.5 %) had proctitis. Extraintestinal manifestations were rare and only one patient had pyoderma gangrenosum. One patient developed multifocal colorectal cancer10 years after the inial diagnosis of UC and died 2 years later due to metastases. Histology plays an important role in the diagnosis and man agementof patients with UC.Wenoted a goodcorrelation between clinical and patho logical features. The most recent colonic biopsy showed features of chronic UC with activity in 34 cases and features of remission in 4 cases.